Psychosocial Impact of Acne (Pimples) – Supportive Intervention with Homoeopathy (Homoeopathy for All, 2025)
Acne is one of the most common  skin conditions of all age group  individuals especially among  the teenagers. The clinical  presentation of acne can range from  a mild comedonal form to severe  inflammatory cystic acne of the face,  chest, and back. Acne can occur  during a time of low self-esteem  and high concern about appearance.  This article reviews about causes,  risk factors, different types, clinical  presentation, general management  including some home remedies and  homoeopathic way of treatment  of acne. Homoeopathy treats the  person as a whole. It means that  homoeopathic treatment focuses on  the patient as a person, as well as his  pathological condition.
Keywords: teenagers; pathological condition; loss of confidence; plugged with oil and dead skin cells